Late oesophagus pleural fistula post Pneumenectomy. - Brandolino, Mario; Bertullo, Hugo; Abelleyra, Rodolfo (Cirugía del Uruguay, 1984)
The perforation of the esophagus in the pleural cavity as a late comp'lication after a pneumenectomy is a rare ocurrence but often fatal. A case is presented of a perforation four years alter pneumenectomy of the left lung. Discussed are the pathogenic mechanisms and the treatment used, emphasis being laid on the necessity of promoting aggresive therapeutic measures in view of curren! failure of conservative techniques.